Supine Percutaneous Nephrolithotomy in a Patient with Solitary Lung: A Case Report and Literature Review - Danacıoğlu, Yavuz Onur; Arıkan, Yusuf; Akkaş, Fatih; Şam, Emre; Özlü, Deniz Noyan; Emir, Nalan Saygı; Atar, Feyzi Arda (Prague medical report, 2021)
Percutaneous nephrolithotomy (PNL) surgeries are performed with different patient positions, anesthesia methods and different-sized access sheaths in order to reduce the complication rates. Supine positioned PNL can be performed safely in the high-risk group patients with comorbidities. Herein, we present a patient who had a past surgical history of right pneumonectomy and underwent a supine PNL procedure under regional anesthesia for a staghorn renal stone in the right kidney.
Keywords: Lung; lidé; plíce; perkutánní nefrolitotomie; Humans; Supine; Nephrolithotomy, Percutaneous; Percutaneous nephrolithotomy; Endourology; Solitary lung